2019
DOI: 10.1002/hed.25344
|View full text |Cite
|
Sign up to set email alerts
|

The impact of time after radiation treatment on dysphagia in patients with head and neck cancer enrolled in a swallowing therapy program

Abstract: Background Swallowing dysfunction after radiotherapy (RT) for head and neck cancer can be devastating. A randomized control trial compared swallow exercises versus exercise plus neuromuscular electrical stimulation therapy and found no overall difference in outcomes. Methods Quality of life (QOL), diet, and swallowing variables collected at discrete intervals on 117 patients were reanalyzed to test the hypothesis that shorter time between the completion of radiotherapy and beginning of the swallowing therapy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The power calculation of this study was made solely on the expected changes in PAS, which also could be considered a limitation. Moreover, the random allocation did not include time since oncologic treatment which may have had an impact on the results, since a recent study has found that swallowing therapy that was initiated within 1 year after radiotherapy resulted in better outcomes than for patients with later swallowing intervention 76 . However, no statistically significant differences were found between the groups regarding time from oncologic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The power calculation of this study was made solely on the expected changes in PAS, which also could be considered a limitation. Moreover, the random allocation did not include time since oncologic treatment which may have had an impact on the results, since a recent study has found that swallowing therapy that was initiated within 1 year after radiotherapy resulted in better outcomes than for patients with later swallowing intervention 76 . However, no statistically significant differences were found between the groups regarding time from oncologic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Also, dysphagia has been found to be one of the most commonly reported late side effects after radiotherapy, 16,18 with 45% of patients reporting it 2 years after IMRT. [19][20][21][22] Motz et al observed the highest incidence of dysphagia, airway obstruction, and pneumonia in the first year after treatment but without a significant decrease in the subsequent four years. 9 Limited studies have assessed toxicity >2 years after therapy.…”
Section: Introductionmentioning
confidence: 99%
“…9 Limited studies have assessed toxicity >2 years after therapy. [19][20][21][22] Motz et al observed the highest incidence of dysphagia, airway obstruction, and pneumonia in the first year after treatment but without a significant decrease in the subsequent four years. 22 The study by Kirsh et al assessed very late dysphagia (>3 years after IMRT) and saw that 23% of the patients still required a modified diet after a mean follow-up time of 4.55 years.…”
Section: Introductionmentioning
confidence: 99%
“…QOL and diet scores improved most among those who started therapy <1 year after RT, with little improvement evident among those who started therapy more than 2 years post-RT. 20 Clinical experience supports that survivors with late-RAD almost universally present with palpable, high-grade cervical fibrosis. Fibrosis is thought to compress peripheral nerve tracts, thereby contributing to denervation of critical swallowing muscles.…”
Section: Introductionmentioning
confidence: 92%